BRAND LOVE AS A BRIDGE BETWEEN ONLINE BRAND EXPERIENCE AND LOYALTY: EVIDENCE FROM INDIA’S ONLINE RETAIL SECTOR - 1 Mr. Mohd Altaf Wani, 2 Professor Iqbal Ahmad Hakim, 3 Mr. Aadil Shaban Lone (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This study examined how brand love mediates the relationship between online brand experience and brand loyalty in Jammu and Kashmir's online retail sector. Exploratory and confirmatory factor analysis (EFA and CFA) were used to evaluate the measurement model using data collected from the students of higher education. Path analysis supported all hypotheses by showing substantial correlations between online brand experience, brand love, and brand loyalty. The findings emphasize the need of great brand experiences to build consumer loyalty through emotional ties. The study showed Indian online businesses how emotional interaction builds long-term customer relationships. These findings strengthen digital brand management knowledge and help strategists increase consumer retention through brand love.